Viability and Alkaline Phosphatase Activity of Human Dental Pulp Cells after Exposure to Yellowfin Tuna Bone-Derived Hydroxyapatite In Vitro - Tetiana Haniastuti; Heni Susilowati; Margareta Rinastiti (International Journal of Dentistry)
The bone of yellowfin tuna (Thunnus albacares) contains high calcium and phosphor and can be synthesized into hydroxyapatite (HA). Due to its mineral content and similarity in chemical composition with human hard tissue, HA may have potency as a pulp capping material. The aim of this in vitro study was to evaluate the viability and alkaline phosphatase (ALP) activity of dental pulp cells after exposure to HA synthesized from yellowfin tuna bone (THA). Pulp cells were isolated from human-impacted third molar. To evaluate the viability of the pulp cells, the cells were cultured and exposed to various concentrations (6.25 to 200 μg/ml) of THA for 24, 48, and 72 hours. For ALP activity assay, pulp cells were cultured with odontoblastic differentiation media and exposed to THA for 7, 11, and 15 days. ALP activity was then determined using an ALP colorimetric assay kit. Results showed that the viability of the cells was more than 91% after exposure to various concentrations of THA and the cells demonstrated normal cell morphology in all observation periods. The ALP activity test revealed that groups exposed to THA for 7, 11, and 15 days showed higher ALP activity than the control groups (p<0.05). It is concluded that THA had no cytotoxic effect on pulp cells; furthermore, it enhanced proliferation as well as ALP activity of the pulp cells.